Epidemiology of acute coronary syndrome and heart failure in Latin America (2011)
Cardiovascular disease is the principle cause of death in Latin America. Data from the World Health Organization indicate that the region is currently experiencing a large-scale epidemic of cardiovascular disease. This could be attributable to demographic and lifestyle changes inherent in the epidemiologic transition: one consequence of increased life-expectancy is longer exposure to cardiovascular risk factors, which results in a higher probability of adverse events. Latin America is one of the regions of the world with the highest burden of cardiovascular risk factors, particularly overweight, dyslipidemia and diabetes mellitus. These factors will have a significant impact on the incidence of coronary events and heart failure in the near future. In addition, infectious conditions, especially Chagas disease and rheumatic fever, affect large sections of the population in the region. Unless preventive measures are introduced in the next three to four decades, the number of deaths due to cardiovascular disease in the region will increase by more than 200%. Data currently available indicate that mortality in patients with acute coronary syndrome is greater in Latin America than in developed countries. Among the possible factors that could explain this finding are the underuse of therapies that have been shown to be effective and the more conservative and later use of surgical and percutaneous interventions. In Latin America, heart failure occurs in younger subjects than in the rest of the world and is most frequently related to ischemic heart disease. However, Chagas disease is close to hypertension as the second most common cause. There is an urgent need for well-designed epidemiologic studies to guide the implementation of preventive measures and appropriate treatment. © 2011 Sociedad Española de Cardiología. Publicado por Elsevier España, SL. Todos los derechos reservados.